Corporate Sustainability in Fashion Industry - Yu, Dian (2017)
This paper combines empirical analysis and findings of qualitative research to understand the sustainable strategies of fashion industry. Firstly, I chose customers of fashion industry and did interviews to collect their opinions of sustainability management. Secondly I chose two leader companies of this industry, which are Zara and Louis Vuitton as examples to analyze their strategies by using value chain models. Then the findings of empirical analysis and qualitative research show corporate sustainable strategies not only are workable but also created competitive advantages for companies in fashion industry. So I argue that is necessary for fashion industry to have more sustainable strategies in the near future.